Keris dalam Masyarakat Melayu Jambi: Kajian Etnolinguistik - Fikriya, Maisan Ashfa; Khotimah, Khusnul; Tampubolon, Gita Novelia; Fitriah, Siti (Prosiding Seminar Nasional Humaniora, 2025)
This article discusses the lexical and cultural meanings of various traditional keris of the Jambi Malay community, such as Keris Siginjei, Keris Cundrik, and Keris Singa Merjaya, along with supporting photos and texts, using an ethnolinguistic approach. This study aims to reveal the cultural, historical, and spiritual values attached to these keris and their role in shaping the identity of the Malay community in Jambi. The method used is qualitative descriptive analysis, which examines both the literal (lexical) and symbolic (cultural) meanings of each object of study. The results of the study show that the keris is not merely a physical tool, but also a symbol of power, resistance, spirituality, and diplomatic relations in the context of the Jambi Sultanate. In conclusion, the keris as an artifact is a concrete manifestation of the interconnection between language, symbols, and culture that deeply reflects the identity and noble values of the Jambi Malay community. Abstrak Penelitian ini membahas makna leksikal dan kultural dari berbagai keris tradisional masyarakat Melayu Jambi dengan menggunakan pendekatan etnolinguistik. Penelitian ini bertujuan mengungkap nilai budaya, sejarah, dan spiritual yang melekat pada keris-keris tersebut serta peranannya dalam membentuk identitas masyarakat Melayu Jambi. Metode yang dipakai adalah analisis deskriptif kualitatif yang memeriksa makna harfiah (leksikal) sekaligus makna simbolis budaya (kultural) dari setiap objek studi. Hasil penelitian menunjukkan bahwa keris bukan sekadar alat fisik, melainkan juga merupakan simbol kekuasaan, perlawanan, spiritualitas, dan hubungan diplomatik dalam konteks Kesultanan Jambi. Kesimpulannya, keris sebagai artefak adalah manifestasi konkrit dari keterkaitan antara bahasa, simbol, dan budaya yang mencerminkan identitas serta nilai-nilai luhur masyarakat Melayu Jambi secara mendalam.